Endowments in Islamic Law and their Impact on the Care of People with Special Needs - Dr. Abdussalam Alhadi Alazhari (Journal of Scientific and Human Dimensions, 2026)
The research aims to clarify the status and importance of endowment work in Islamic law, and to highlight endowment efforts that would contribute to the advancement of people with special needs in various fields, including education, health, recreation, and innovation of programs through which they can be integrated into society. The concept of endowment work. The research concluded that Islamic endowment is of great importance in social solidarity, especially with regard to people with special needs, that it is one of the most important financial resources in the success of development projects, and that continuous support for people with special needs, especially in the scientific aspect, makes them creative and distinguished at all levels.